Carbon crystal material and preparation method thereof, battery negative electrode lead paste, battery negative electrode plate and preparation method thereof, lead-acid battery

By using carbon crystal material as the additive for the negative electrode of the battery in lead-acid batteries, the problems of low energy density and short cycle life of traditional lead-acid batteries are solved, and higher energy density and longer cycle life are achieved.

CN118598114BActive Publication Date: 2025-04-18NINE INTELLIGENT CHANGZHOU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410758774.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-04-07
Filing Date
2024-06-12
Publication Date
2025-04-18
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

Traditional lead-acid batteries have problems with low energy density and short cycle life, which limits their application range.

Method used

Carbon crystal material is used as the additive to the negative electrode of the battery, and the carbon source solution is mixed with the catalyst liquid to form a gel-like dispersion precursor, and presintering and high-temperature carbonization are performed in a high-temperature tube furnace to promote carbon crystal growth.

Benefits of technology

It improves the conductivity and utilization of active substances of the battery, optimizes the electrode structure, enhances the energy density and capacity of the battery, and extends the cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118598114B_ABST
    Figure CN118598114B_ABST
Patent Text Reader

Abstract

The embodiments of the present invention provide a carbon crystal material and a preparation method thereof, a battery negative electrode lead paste, a battery negative electrode plate and a preparation method thereof, and a lead-acid battery. In the preparation of the carbon crystal material, a carbon source solution and a catalyst liquid are mixed into a gel-like dispersion precursor, which is then placed in a high-temperature tubular furnace, and subjected to pre-sintering and high-temperature carbonization treatment under an inert gas protective gas environment to grow carbon crystals. After the carbon crystal growth is completed, an inert gas protective gas is continuously introduced. After the reaction temperature drops to room temperature, a carbon crystal material is obtained. This carbon crystal material can be used in the preparation of battery negative electrode lead paste, battery negative electrode plate and lead-acid battery, and can provide functions such as high conductivity, high specific surface area and good mechanical properties, which helps to improve the discharge efficiency and output power of lead-acid batteries and extend their cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a carbon crystal material and a preparation method thereof, a battery negative electrode lead paste, a battery negative electrode plate and a preparation method thereof, and a lead-acid battery. Background Art

[0002] Lead-acid batteries, as a common energy storage device, have been invented for more than 100 years since 1958. Lead-acid batteries have the advantages of low cost, simple structure, easy use, abundant and easy-to-obtain raw material resources, etc. They play an important role in chemical power sources and have become an indispensable energy product in social production and human life. They are widely used in electric vehicles, UPS power supplies and other fields. However, traditional lead-acid batteries have problems such as low energy density and short cycle life, which limit their application scope. Summary of the invention

[0003] Multiple aspects of the present application provide a carbon crystal material and a preparation method thereof, a battery negative electrode lead paste and a negative electrode plate, and a lead-acid battery to solve one or more of the above-mentioned problems.

[0004] An embodiment of the present application provides a method for preparing a carbon crystal material, comprising: mixing a carbon source solution and a catalyst liquid into a gel-like dispersion liquid precursor; placing the dispersion liquid precursor in a high-temperature tube furnace, and subjecting the dispersion liquid precursor to pre-sintering and high-temperature carbonization treatment in an inert gas protective gas environment to grow carbon crystals; and after the growth of the carbon crystals is completed, continuously introducing the inert gas protective gas into the high-temperature tube furnace and maintaining the reaction temperature until it drops to room temperature, thereby obtaining the carbon crystal material.

[0005] In some embodiments of the preparation method, the carbon source solution is prepared by dispersing a biomass carbon source in water, wherein the biomass carbon source is one of glucose, sucrose, starch and a combination thereof, and the concentration of the biomass carbon source is 0.1 to 0.5 mol / L.

[0006] In some embodiments of the preparation method, the catalyst liquid is prepared from ferrocene and a hydrogen bond donor in a mass ratio of 1 to 1.5:1, wherein the hydrogen bond donor is one of xylene, ethanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, glycerol, urea and a combination thereof.

[0007] In some embodiments, the preparation method also includes a procedure of heating and stirring the catalyst liquid, and after the carbon source solution and the catalyst liquid are mixed, ultrasonic oscillation is performed for 10 to 20 minutes, and then allowed to stand for 12 to 24 hours before heating and stirring to form the dispersion precursor.

[0008] In some embodiments of the preparation method, the heating and stirring is stirring at a temperature of 60 to 120° C. for 1 to 5 hours.

[0009] In some embodiments of the preparation method, the pre-sintering is carried out under the conditions of heating rate of 2-10°C / min, heating to 250-500°C, and keeping warm for 1-4h, wherein the inert gas shielding gas is argon or a composite shielding gas mixed with argon and hydrogen.

[0010] In some embodiments of the preparation method, the carbon crystal growth is carried out under argon protective gas, at a heating rate of 2-10° C. / min, heating to 800-1250° C., and keeping the temperature for 2-6 hours.

[0011] In some embodiments, the preparation method further comprises cooling, washing and drying the carbon crystal material, and forming a micro-nano carbon crystal material after grinding and screening.

[0012] The present application also provides a carbon crystal material, which is prepared by any of the above-mentioned preparation methods.

[0013] The present application also provides a battery negative electrode lead paste, comprising the following components in percentage by mass: the carbon crystal material as described above: 0.5-2%; red lead: 10-15%; high-strength short fiber: 0.1-0.3%; lignin: 0.1-0.3%; humic acid: 0.5-1%; stearic acid: 0.1-0.3%; barium sulfate: 0.5-2%; water: 10-15%; dilute sulfuric acid: 10-13%; the rest is sponge lead, and the sum of the percentages by mass of the components is 100%.

[0014] The present application further provides a method for preparing a negative electrode plate of a battery, comprising: uniformly mixing a certain amount of the above-mentioned carbon crystal material, high-strength short fibers, lignin, barium sulfate, stearic acid, humic acid, red lead, and sponge lead; adding a certain amount of water and a certain amount of dilute sulfuric acid, stirring the raw materials into a lead paste to obtain a negative electrode lead paste for a battery, wherein the negative electrode lead paste for a battery comprises the following components by mass percentage: 0.5% to 2% of the carbon crystal material; 10% to 15% of the red lead; and 0.5% to 2% of the high-strength short fibers. The fiber: 0.1-0.3%; the lignin: 0.1-0.3%; the humic acid: 0.5-1%; the stearic acid: 0.1-0.3%; the barium sulfate: 0.5-2%; the water: 10-15%; the dilute sulfuric acid: 10-13%; the rest is the sponge lead, and the sum of the mass percentages of all components is 100%; and the battery negative electrode lead paste is molded to obtain a grid blank, and then passed through a high-temperature curing furnace at 65°C to 85°C.

[0015] The present application also provides a battery negative electrode plate, which is prepared by the above-mentioned method for preparing a battery negative electrode plate.

[0016] The present application also provides a lead-acid battery, which is assembled using the above-mentioned battery negative plate as the negative electrode.

[0017] In the embodiments of the present application, the raw materials used in the preparation method of the carbon crystal material are common and easy to obtain, the reaction system involved has simple components, the reaction conditions are controllable, the preparation process is simple and easy, it has the advantages of environmental protection, low equipment requirements and no geographical restrictions, and is suitable for large-scale industrial production of carbon crystal materials and subsequent battery negative lead paste and battery negative plates. More importantly, the cycle life and high current charge and discharge capacity of lead-acid batteries using this carbon crystal material have been improved.

[0018] Specifically, the carbon crystal material obtained by this preparation method can be used as an additive for the negative electrode of the battery to improve the conductivity and utilization rate of the active material of the electrode and optimize the electrode structure. Its advantages include: (1) high conductivity: this carbon crystal material has excellent conductivity, and the carbon crystal material arranged in an array can form a tighter conductive network, reduce the internal resistance of the battery, thereby ensuring the smooth transmission of the current inside the battery and improving the discharge efficiency and power output of the battery; (2) high specific surface area: the micro-nano carbon crystal material has a large specific surface area and can contact with more electrolyte, thereby improving the reaction activity inside the battery and further increasing the energy density and capacity of the battery; and (3) good mechanical properties: the carbon crystal material has excellent mechanical properties and can be used as a structural support material for the battery, which helps to enhance the stability of the battery and reduce the deformation and damage of the battery during the charging and discharging process, thereby reducing the performance degradation of the battery during long-term use and extending the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0020] Figure 1 This is a flow chart of a method for preparing a carbon crystalline material according to an embodiment of the present application.

[0021] Figure 2 This is a SEM image of the carbon crystal material of the embodiment of the present application.

[0022] Figure 3 This is a SEM image of the negative electrode plate of the battery according to an embodiment of the present application.

[0023] Figure 4 This is a test diagram of conventional battery cycle experiments for the embodiments of the present application and the comparative examples. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the specific embodiments of the present application and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0025] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.

[0026] Please refer to Figure 1 , the present application embodiment provides a carbon crystal material, and the preparation method thereof includes:

[0027] The carbon source solution and the catalyst liquid are mixed into a gel-like dispersion liquid precursor (S101). In this step, the carbon source solution and the catalyst liquid are configured separately, for example, the biomass carbon source is dispersed in water to form a carbon source solution, and ferrocene and a hydrogen bond donor are mixed into a catalyst liquid. In some embodiments of the present application, the biomass carbon source can be selected from one or more of glucose, sucrose and starch, and is configured into a carbon liquid solution with a biomass carbon source concentration of 0.1 to 0.5 mol / L in deionized water. And, in some embodiments of the present application, ferrocene and a hydrogen bond donor are mixed into a catalyst liquid in a mass ratio of 1 to 1.5:1, for example, ferrocene and a hydrogen bond donor are mixed in a mass ratio of 1:1, 1.3:1 or 1.5:1, and then stirred at a temperature of 60 to 120°C for 1 to 5 hours to form a catalyst liquid. The hydrogen bond donor may be, but is not limited to, one of xylene, ethanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, glycerol and urea, or a combination of the above hydrogen bond donors.

[0028] It is worth noting that in the preparation method of the carbon crystal material provided in the embodiment of the present application, ferrocene, as an organic metal compound, has a π-coordination structure, that is, a special coordination bond is formed between the cyclopentadienyl group and the transition metal iron, and this structure makes it play an important role in organic synthesis and catalytic reactions. In the subsequent step of synthesizing the carbon crystal material, the vinyl derivative of ferrocene can undergo olefin polymerization to obtain a metal-containing polymer with a carbon chain skeleton. At the same time, ferrocene can also improve the performance and stability of the carbon crystal material.

[0029] In addition, in some embodiments of the present application, after the carbon source solution and the catalyst liquid are mixed, an ultrasonic oscillation treatment step is performed, for example, ultrasonic oscillation treatment is performed for 10 to 20 minutes, and after standing for 12 to 24 hours, heating and stirring are performed to form a gel-like dispersion precursor.

[0030] Next, the dispersion liquid precursor is placed in a high-temperature tube furnace, and is subjected to pre-sintering and high-temperature carbonization treatment under an inert gas shielding gas environment to allow carbon crystals to grow (S103). After the gel-like dispersion liquid precursor is prepared, it is pushed into a high-temperature tube furnace where a carrier is placed for pre-sintering and high-temperature carbonization growth treatment. For example, before or after the gel-like dispersion liquid precursor is prepared, a cleaned and dried quartz sheet is loaded into a quartz tube as a carrier, and the quartz tube is loaded into a constant temperature zone in the middle of the high-temperature tube furnace for preheating. Subsequently, the quartz tube is taken out, the dispersion liquid precursor is loaded into the quartz tube carrier at a uniform speed, and is pushed into the high-temperature tube furnace. Subsequently, an inert gas shielding gas is introduced into the high-temperature tube furnace, and a carbon crystal growth procedure is performed through pre-sintering and high-temperature carbonization growth treatment.

[0031] In some embodiments of the present application, the dispersion precursor is heated to 250-500°C for pre-sintering at a heating rate of 2-10°C / min in an environment of a composite protective gas mixed with argon and hydrogen, and maintained at this temperature for 1-4 hours to complete the pre-sintering procedure. The carbon crystal growth can be, but is not limited to, heated to 800-1250°C at a heating rate of 2-10°C / min in an environment of argon protective gas, and then maintained for 2-6 hours to complete the high-temperature carbonization treatment procedure.

[0032] After the carbon crystal growth is completed, an inert gas protection gas is continuously introduced into the high-temperature tube furnace and maintained until the reaction temperature drops to room temperature to obtain a carbon crystal material (S105). The SEM (Scanning Electron Microscope) image thereof is as follows: Figure 2 shown.

[0033] The carbon crystal material obtained by the above preparation method can be used in many aspects, for example, in the preparation of lead-acid batteries as a component material of battery negative electrode lead paste.

[0034] In some embodiments of the present application, a certain amount of carbon crystal material, high-strength short fiber, lignin, barium sulfate, stearic acid, humic acid, red lead and sponge lead are mixed evenly, and a certain amount of water (such as deionized water) is added, and then a certain amount of dilute sulfuric acid, such as dilute sulfuric acid with a concentration of 1.4 g / mL, is slowly added. Then, a mixture in which each raw material is evenly dispersed is obtained by stirring until it is stirred into a paste state to obtain a negative lead paste for a battery.

[0035] Among them, the battery negative electrode lead paste includes the following components in mass percentage: carbon crystal material: 0.5-2%; red lead: 10-15%; high-strength short fiber: 0.1-0.3%; lignin: 0.1-0.3%; humic acid: 0.5-1%; stearic acid: 0.1-0.3%; barium sulfate: 0.5-2%; deionized water: 10-15%; dilute sulfuric acid: 10-13%; the rest is sponge lead, and the sum of the mass percentages of all components is 100%.

[0036] It is understandable that in the preparation process of the above-mentioned battery negative electrode lead paste, the carbon crystal material can be further cooled, cleaned and dried, and after being ground and sieved into micro-nano carbon crystal material, it is added to other materials for stirring. In this way, the micro-nano carbon crystal material has a high specific surface area in the battery negative electrode lead paste, thereby improving the conductivity.

[0037] Next, the negative lead paste of the battery is molded to obtain a grid blank, and then the negative electrode plate of the battery is obtained after a high-temperature curing process of 65°C to 85°C and a reaction of the active material for 24h to 48h in a high-temperature curing furnace. Figure 3 Afterwards, the negative plate of the battery is assembled as a negative electrode in a lead-acid battery.

[0038] Among them, from Figure 2 and Figure 3 It can be seen that the carbon crystal material of the embodiment of the present application has a high specific surface area and high electrical conductivity, and the black carbon crystal material links the negative electrode active material particles of the lead-acid battery like a conductive fiber bundle, which can greatly improve the charging acceptance capacity and cycle life of the lead-acid battery.

[0039] The following further illustrates the carbon crystal material provided in the embodiments of the present application and the technical effects produced when the carbon crystal material is applied to lead-acid batteries by comparing some embodiments of the present application with comparative examples.

[0040] Embodiment 1:

[0041] Sucrose was added as a biomass carbon source to deionized water and mixed to prepare a 0.3 mol / L sucrose solution as a carbon source solution, and a mixture of xylene and ferrocene with a mass ratio of 1.2:1 was prepared as a catalyst solution. Then, the sucrose solution was added to the catalyst solution and ultrasonically vibrated for 15 minutes, then allowed to stand for 12 hours, and then stirred at 90°C for 1 hour to obtain a gel-like dispersion precursor containing carbon crystal materials. The cleaned and dried quartz sheet was loaded into a quartz tube as a carrier, and the quartz tube was loaded into the constant temperature zone in the middle of a high-temperature tube furnace. Subsequently, the dispersion precursor was loaded into the quartz tube carrier and pushed into the high-temperature tube furnace. Argon and hydrogen were introduced into the high-temperature tube furnace as protective gases, and the temperature was increased from 25°C to 400°C at a heating rate of 2°C / min, and then the temperature was kept for 3 hours for pre-sintering. Then, under the protection of argon, the temperature was increased to 900°C at 2°C / min and sintered for 4 hours for high-temperature carbonization treatment to promote carbon crystal growth. After the carbon crystal growth is completed, argon gas is continuously introduced and maintained until the temperature of the high-temperature tube furnace drops to room temperature, and then the quartz sheet carrier is taken out to obtain the carbon crystal material.

[0042] Next, a certain amount of carbon crystal material, high-strength short fiber, lignin, barium sulfate, stearic acid, humic acid, red lead, and sponge lead are mixed evenly, and then a certain amount of deionized water is added, and a certain amount of dilute sulfuric acid with a concentration of 1.4g / mL is slowly added, and a mixture of the raw materials is obtained by stirring, and stirred into a lead paste to complete the preparation of the negative electrode lead paste of the battery. Among them, the negative electrode lead paste of the battery includes the following components by mass percentage: carbon crystal material: 1.2%; red lead: 10%; high-strength short fiber: 0.1%; lignin: 0.2%; humic acid: 0.2%; stearic acid: 0.1%; barium sulfate: 1.6%; deionized water: 11%; dilute sulfuric acid with a concentration of 1.4g / mL: 10.6%; the rest is sponge lead, and the sum of the mass percentages of all raw materials is 100%.

[0043] Then, the negative lead paste of the battery is molded into a grid blank, and the active material reacts through a high-temperature curing process of 85° C. for 24 hours in a high-temperature curing furnace to obtain a negative electrode plate of the battery.

[0044] Embodiment 2:

[0045] Glucose was added as a biomass carbon source to deionized water and mixed to prepare a 0.3 mol / L glucose solution as a carbon source solution, and a mixture of xylene and ferrocene with a mass ratio of 1.5:1 was prepared as a catalyst solution. Then, the glucose solution was added to the catalyst solution and ultrasonically vibrated for 15 minutes, then allowed to stand for 24 hours, and then stirred at 90°C for 1 hour to obtain a gel-like dispersion precursor containing carbon crystal materials. The cleaned and dried quartz sheet was loaded into a quartz tube as a carrier, and the quartz tube was loaded into the constant temperature zone in the middle of a high-temperature tube furnace. Subsequently, the dispersion precursor was loaded into the quartz tube carrier and pushed into the high-temperature tube furnace. Argon and hydrogen were introduced into the high-temperature tube furnace as protective gases, and the temperature was increased from 25°C to 500°C at a heating rate of 2°C / min, and then the temperature was kept for 2 hours for pre-sintering. Then, under the protection of argon, the temperature was increased to 1200°C at 2°C / min and sintered for 2 hours for high-temperature carbonization treatment to promote carbon crystal growth. After the carbon crystal growth is completed, argon gas is continuously introduced and maintained until the temperature of the high-temperature tube furnace drops to room temperature, and then the quartz sheet carrier is taken out to obtain the carbon crystal material.

[0046] Next, the preparation of the negative electrode lead paste and the negative electrode plate of the battery is substantially the same as in Example 1. The difference between the two is that the negative electrode lead paste of the battery in Example 2 includes the following components by mass percentage: carbon crystal material: 1.5%; red lead: 10%; high-strength short fiber: 0.1%; lignin: 0.2%; humic acid: 0.1%; stearic acid: 0.1%; barium sulfate: 1.6%; deionized water: 11.1%; dilute sulfuric acid with a concentration of 1.4 g / mL: 10.6%; the rest is sponge lead, and the sum of the mass percentages of all raw materials is 100%.

[0047] Embodiment 3:

[0048] Sucrose was added as a biomass carbon source to deionized water and mixed to prepare a 0.4 mol / L sucrose solution as a carbon source solution, and a mixture of xylene and ferrocene with a mass ratio of 1:1 was prepared as a catalyst solution. Then, the sucrose solution was added to the catalyst solution and ultrasonically vibrated for 10 minutes, then allowed to stand for 24 hours, and then stirred at 90°C for 1 hour to obtain a gel-like dispersion precursor containing carbon crystal materials. The cleaned and dried quartz sheet was loaded into a quartz tube as a carrier, and the quartz tube was loaded into the constant temperature zone in the middle of a high-temperature tube furnace. Subsequently, the dispersion precursor was loaded into the quartz tube carrier and pushed into the high-temperature tube furnace. Argon and hydrogen were introduced into the high-temperature tube furnace as protective gases, and the temperature was increased from 25°C to 350°C at a heating rate of 2°C / min, and then the temperature was kept for 2 hours for pre-sintering. Then, under the protection of argon, the temperature was increased to 1100°C at 2°C / min for 3 hours for high-temperature carbonization treatment to promote carbon crystal growth. After the carbon crystal growth is completed, argon gas is continuously introduced and maintained until the temperature of the high-temperature tube furnace drops to room temperature, and then the quartz sheet carrier is taken out to obtain the carbon crystal material.

[0049] Next, a certain amount of carbon crystal material, high-strength short fiber, lignin, barium sulfate, stearic acid, humic acid, red lead, and sponge lead are mixed evenly, and then a certain amount of deionized water is added, and a certain amount of dilute sulfuric acid with a concentration of 1.4 g / mL is slowly added, and a mixture of the raw materials is obtained by stirring, and stirred into a lead paste to complete the preparation of the negative electrode lead paste of the battery. Among them, the negative electrode lead paste of the battery includes the following components by mass percentage: carbon crystal material: 1.0%; red lead: 10%; high-strength short fiber: 0.2%; lignin: 0.2%; humic acid: 0.2%; stearic acid: 0.1%; barium sulfate: 1.6%; deionized water: 11.5%; dilute sulfuric acid with a concentration of 1.4 g / mL: 10.3%; the rest is sponge lead, and the sum of the mass percentages of all raw materials is 100%.

[0050] Then, the negative lead paste of the battery is molded into a grid blank, and the active material reacts by a high-temperature curing process of 65° C. for 48 hours in a high-temperature curing furnace to obtain a negative electrode plate of the battery.

[0051] Comparative Example 1:

[0052] Sucrose is added as a biomass carbon source to deionized water to mix and prepare a 0.5 mol / L sucrose solution, and then the sucrose solution is transferred to a hydrothermal reaction tank. The hydrothermal reaction tank is placed in a constant temperature box, heated to 250°C at 2°C / min and kept warm for 6 hours. After natural cooling, it is taken out and washed with deionized water and ethanol three times respectively, and then dried in a drying oven at 60°C for 2 hours to obtain black carbon crystal solid particles. Next, a xylene solution is prepared, and the black carbon crystal solid particles are added to the xylene solution, and stirred at 90°C for 1 hour to obtain a carbon crystal precursor. The cleaned and dried quartz sheet is loaded into a quartz tube as a carrier, and the quartz tube is loaded into the constant temperature zone in the middle of the high-temperature tube furnace. Subsequently, the carbon crystal precursor is loaded into the quartz tube carrier and pushed into the high-temperature tube furnace. Argon and hydrogen were introduced into a high-temperature tube furnace as protective gases, and the temperature was increased from 25°C to 350°C at a rate of 2°C / min, and the temperature was kept for 2 hours for pre-sintering, and then the temperature was increased to 1100°C at 2°C / min and sintered for 5 hours under the protection of argon. After the carbon crystal growth was completed, argon was continuously introduced until the temperature of the reaction device dropped to room temperature, and the quartz sheet carrier was taken out to obtain the carbon crystal material of Comparative Example 1.

[0053] Next, a certain amount of micro-nano carbon crystal material, high-strength short fiber, lignin, barium sulfate, stearic acid, humic acid, red lead, and sponge lead are mixed evenly, and then a certain amount of deionized water is added, and a certain amount of dilute sulfuric acid with a concentration of 1.4 g / mL is slowly added, and a mixture in which each raw material is evenly dispersed is stirred to a lead paste to obtain the battery negative electrode lead paste of Comparative Example 1. Among them, in the battery negative electrode lead paste of Comparative Example 1, the raw materials include by mass percentage: carbon crystal material: 1.0%; red lead: 10%; high-strength short fiber: 0.2%; lignin: 0.2%; humic acid: 0.1%; stearic acid: 0.1%; barium sulfate: 1.6%; deionized water: 12%; dilute sulfuric acid with a concentration of 1.4 g / mL: 9%; the rest is sponge lead, and the sum of the mass percentages of all raw materials is 100%.

[0054] Then, the negative electrode lead paste of the battery of comparative example 1 was molded into a grid body, and the active material was reacted by a high temperature curing process at 85° C. for 24 hours in a high temperature curing furnace to obtain the negative electrode plate of the battery of comparative example 1.

[0055] Comparative Example 2: The difference between Comparative Example 2 and Comparative Example 1 is that the mass ratio of xylene and ferrocene in the catalyst solution is 2:1.

[0056] Comparative Example 3: The difference between it and Comparative Example 1 is that no carbon crystal material is added. The battery negative electrode lead paste of Comparative Example 3 includes the following components by mass percentage: red lead: 10%; high-strength short fiber: 0.2%; lignin: 0.2%; humic acid: 0.1%; stearic acid: 0.1%; barium sulfate: 1.6%; deionized water: 12%; dilute sulfuric acid with a concentration of 1.4 g / mL: 9%; the rest is sponge lead, and the sum of the mass percentages of all raw materials is 100%.

[0057] Test examples and test results:

[0058] The negative electrode plates of the batteries obtained in Examples 1 to 3 of the present application and the negative electrode plates of the batteries obtained in Comparative Examples 1 to 3 were assembled into experimental batteries according to the ratio of 4 positive plates to 5 negative plates. Then, a special electrolyte for internalization was added for internalization charging, and after the charging was completed, a 60V20Ah lead-acid battery pack was assembled to perform a basic charging acceptance capacity test and a cycle life test of the battery.

[0059] The test results of basic charging reception capability are shown in Table 1 below:

[0060] Table 1

[0061] Charging receiving capacity (A) Example 1 12 Example 2 12 Example 3 12 Comparative Example 1 4 Comparative Example 2 5 Comparative Example 3 4

[0062] It can be seen from Table 1 that the charge acceptance of the lead-acid battery in the embodiment of the present application is 2 to 3 times more than that of the comparative lead-acid battery, indicating that its charge acceptance is stronger.

[0063] Then the battery was subjected to a conventional 100% DOD cycle test, and the cycle regime was as follows:

[0064] 1) Discharge the battery to 1.5V / battery;

[0065] 2) Charge at 3A constant voltage 14.8V / battery until the current is less than 0.6A;

[0066] 3) Charge at 13.8V / cell for 1.5h.

[0067] The experimental results are shown in Table 2 and Figure 3 shown.

[0068] Table 2

[0069] Cycle life (times) Example 1 1205 Example 2 1153 Example 3 1087 Comparative Example 1 519 Comparative Example 2 477 Comparative Example 3 341

[0070] From Table 2 and Figure 3 It can be seen from the test results that the 100% DOD cycle life of the lead-acid battery in the embodiment of the present application exceeds 1000 times, while the cycle life of the lead-acid battery in the comparative example is 300 to 500 times, indicating that the carbon crystal material prepared in the embodiment of the present application, when applied to lead-acid batteries, helps to improve the cycle life of the lead-acid batteries and plays a significant role in improving them.

[0071] In general, in the preparation of the carbon crystal material provided in the embodiments of the present application, the carbon source solution and the catalyst liquid are directly mixed and sintered, instead of the conventional process of preparing the carbon source solution into carbon powder or carbon ball particles and then adding the catalyst solution for mixing and sintering. The advantages are mainly reflected in the following aspects: (1) Uniformity. The direct mixing and sintering method can mix the carbon source and the catalyst at the molecular level to ensure that the catalyst is evenly distributed in the carbon source. This helps to form a uniform carbon crystal structure in the subsequent sintering process and improve the overall performance of the material. (2) Reaction efficiency. Since the catalyst liquid is directly mixed with the carbon source solution, the contact area between the catalyst and the carbon source is larger, thereby improving the efficiency of the catalytic reaction. This helps to achieve the formation of carbon crystals at a lower sintering temperature and save energy. (3) Controllability. The direct mixing method can better control the morphology, size and structure of the carbon crystal during growth. By adjusting the concentration, ratio and mixing conditions of the carbon source solution and the catalyst liquid, the carbon crystal growth process can be accurately regulated, thereby obtaining a carbon crystal material or a micro-nano carbon crystal material with the desired specific properties. (4) Simplified process: Compared with the traditional synthesis method of adding carbon powder or carbon sphere particles to a catalyst liquid, the direct mixing and sintering method in the embodiment of the present application eliminates the preparation and dispersion process of carbon powder or carbon sphere particles, thus simplifying the process steps. This not only improves production efficiency, but also helps reduce production costs.

[0072] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A battery negative electrode lead paste, characterized in that: include: The following components by mass percentage: Carbon crystal material: 0.5-2%; Red lead: 10-15%; High-strength short fiber: 0.1-0.3%; Lignin: 0.1-0.3%; Humic acid: 0.5-1%; Stearic acid: 0.1-0.3%; Barium sulfate: 0.5-2%; Water: 10-15%; dilute sulfuric acid: 10-13%; The rest is sponge lead, and the sum of the mass percentages of the components is 100%; The carbon source solution and the catalyst liquid are mixed into a gel-like dispersion precursor; the carbon source solution is prepared by dispersing a biomass carbon source in water, wherein the biomass carbon source is one of glucose, sucrose, starch and a combination thereof; the catalyst liquid is prepared by ferrocene and a hydrogen bond donor in a mass ratio of 1 to 1.5:1, wherein the hydrogen bond donor is one of xylene, ethanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, glycerol, urea and a combination thereof; The dispersion precursor is placed in a high-temperature tube furnace, and subjected to pre-sintering and high-temperature carbonization treatment in an inert gas protective gas environment to grow carbon crystals; and after the growth of the carbon crystals is completed, the inert gas protective gas is continuously introduced into the high-temperature tube furnace and maintained until the reaction temperature drops to room temperature, thereby obtaining the carbon crystal material.

2. The battery negative electrode lead paste according to claim 1, characterized in that: The concentration of the biomass carbon source is 0.1-0.5 mol / L.

3. The battery negative electrode lead paste according to claim 1 or 2, characterized in that: The method further comprises heating and stirring the catalyst liquid, and after the carbon source solution and the catalyst liquid are mixed, ultrasonic oscillation is performed for 10 to 20 minutes, and the mixture is allowed to stand for 12 to 24 hours before heating and stirring to form the dispersion precursor.

4. The battery negative electrode lead paste according to claim 3, characterized in that: The heating and stirring is carried out at a temperature of 60 to 120° C. for 1 to 5 hours.

5. The battery negative electrode lead paste according to claim 1, characterized in that: The pre-sintering is carried out under the conditions of heating at a rate of 2 to 10°C / min, heating to 250 to 500°C, and keeping the temperature for 1 to 4 hours, wherein the inert gas protection gas is argon or a composite protection gas mixed with argon and hydrogen.

6. The battery negative electrode lead paste according to claim 1, characterized in that: The carbon crystal growth is carried out under the conditions of argon protective gas, heating speed of 2-10°C / min, heating to 800-1250°C, and keeping the temperature for 2-6h.

7. The battery negative electrode lead paste according to claim 1, characterized in that: The method also includes cooling, cleaning and drying the carbon crystal material, and forming micro-nano carbon crystal material after grinding and screening.

8. A method for preparing a negative electrode plate of a battery, characterized in that: include: Evenly mix a certain amount of the carbon crystal material according to claims 1 to 7, high-strength short fibers, lignin, barium sulfate, stearic acid, humic acid, red lead, and sponge lead; A certain amount of water and a certain amount of dilute sulfuric acid are added, and the raw materials are stirred into a lead paste to obtain a negative electrode lead paste for a battery, wherein the negative electrode lead paste for a battery comprises the following components by mass percentage: 0.5-2% of the carbon crystal material; 10-15% of the red lead; 0.1-0.3% of the high-strength short fiber; 0.1-0.3% of the lignin; 0.5-1% of the humic acid; 0.1-0.3% of the stearic acid; 0.5-2% of the barium sulfate; 10-15% of the water; 10-13% of the dilute sulfuric acid; and the rest is the sponge lead, and the sum of the mass percentages of all the components is 100%; and The battery negative electrode lead paste is molded to obtain a grid blank, and then the grid blank is cured at 65° C. to 85° C. in a high-temperature curing furnace and the active material reacts for 24 h to 48 h to obtain the battery negative electrode plate.

9. A battery negative plate, characterized in that: Prepared by the preparation method described in claim 8.

10. A lead-acid battery, characterized in that: The negative electrode is assembled using the negative electrode plate of the battery as claimed in claim 9 as the negative electrode.

Citation Information

Patent Citations

  • Preparation method of high-capacity negative electrode material

    CN106450176A

  • Preparation method of carbon fiber-carbon nanotube array / silicone resin thermal conductive composite material

    CN107141803A